A Pilot Study on the Side Effects of Using Atypical Antipsychotics in Patients with Schizophrenia on Developing Obsessive-Compulsive Symptoms (European Journal of Behavioral Sciences, 2022)
Aims: This study aimed to investigate the side effects of using Atypical antipsychotics in Patients with Schizophrenia on developing Obsessive-Compulsive symptoms.Method: In this pre-experimental research, 90 hospitalized patients with Schizophrenia who received Atypical antipsychotics were studied. Yale-Brown Obsessive-Compulsive Scale(YBOCS) was used. Results: The mean score of the YBOCS test at the first week(before using atypical antipsychotics), one month(after using Atypical antipsychotics), and two months(after using Atypical antipsychotics) was 12.13, 16.26, 22.64.Obtained data indicates that using Atypical antipsychotics has a significant effect on developing obsessive-compulsive symptoms in patients with Schizophrenia.Conclusion: Atypical antipsychotics can cause obsessive-compulsive symptoms in patients with Schizophrenia.